Effectiveness of Monopoly Learning Media on Ecological Topics Class X SMA/MA - Ulfa, Khalida; Rahmawati, Alfira; Afriansyah, Dini (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to determine the effectiveness of monopoly learning media on ecological topics on student learning outcomes. This research is a quantitative research approach in the form of pre-experimental. The subjects of this study were all students of class X IPA. Collecting data in this study by providing pre-test and post-test sheets, namely before and after using monopoly learning media in learning activities. The results obtained based on the calculation of the effectiveness test, namely before using the monopoly learning media (pre-test) the average value was 56.00 while after using the monopoly learning media (post-test) the average value was 68.00. The scores of the pre-test and post-test showed a difference in students' interest in learning. So it can be concluded that the monopoly learning media on ecological material for class X SMA/MA is considered effective because it is seen to increase student interest in learning and student learning outcomes.